Quantitative comparison between low energy high resolution (LEHR) and medium energy general purpose (MEGP) collimator on nema spect imaging - Paramesivam, Divya (2024)
Nuclear medicine leverages radioactive materials, known as radiopharmaceuticals or radiotracers, for diagnosing and treating diseases. This field uses radionuclide biomarkers to visualize physiological functions and detect abnormalities, such as cancer cells. Imaging tools such as gamma cameras, which record emissions from radiotracers inside the body, are essential to this process. The gamma camera is a crucial imaging device in Nuclear Medicine, enabling two-dimensional imaging of body processes using radiotracers. It aids in disease diagnosis, monitoring heart function, and detecting radioactive energy. The camera's components include a collimator, large-area NaI(Tl) scintillation crystal, light guide, and photomultiplier tubes. Nuclear medicine imaging systems' quality is influenced by factors such as detector and collimator physical characteristics, image reconstruction algorithms, photon attenuation, scattering, and patient motion. The right collimator is crucial for high-quality images, as it limits photon acceptance angle and allows precise information about the photons' initial emission position. The collimator response to gamma rays is determined by hole diameter, septa width, and septa thickness. Nuclear medicine imaging uses four primary collimator types: parallel-hole, diverging-hole, converging-hole, and pinhole. The type of collimator is influenced by hole diameter and septa length. This research aims to compare the image quality obtained using Low Energy High Resolution (LEHR) and Medium Energy General Purpose (MEGP) collimators in nuclear medicine imaging. The study focuses on assessing differences in sensitivity, contrast, resolution, and signal-to-noise ratio (SNR). A phantom study was conducted using a NEMA 2012/IEC 2008 phantom and Tc-99m point source, by using SPECT technique. The GE Discovery NM/CT 670 Pro Gamma Camera was employed, and both LEHR and MEGP collimators were tested. The experiment involved preparing Tc-99m, acquiring images, and analyzing them for image sensitivity, image contrast, resolution, and SNR. The study measured and compared the performance of LEHR and MEGP collimators. The analysis of image sensitivity, image contrast, resolution, and SNR in both LEHR and MEGP collimator revealed significant variations. MEGP collimator showed better image sensitivity and image contrast but also resulted in degraded resolution and higher image noise. Conversely, the LEHR collimator with their smaller and deeper holes, resulted image with profound resolution and reduced image noise. Image acquired from MEGP collimator exhibited average image sensitivity value of 4.716